2006
DOI: 10.1037/0735-7044.120.3.542
|View full text |Cite
|
Sign up to set email alerts
|

Dissociating ventral and dorsal subicular dopamine D₁ receptor involvement in instrumental learning, spontaneous motor behavior, and motivation.

Abstract: A series of experiments investigating the role of dopamine D 1 receptors in the ventral subiculum (vSUB) and dorsal subiculum (dSUB), 2 subregions of the hippocampal formation, found that D 1 receptor antagonism (3.0 nmol/0.5 μl SCH-23390 bilaterally) in the vSUB impaired instrumental learning and performance, reduced break point in progressive ratio (PR) tests, and produced an intrasession decline in responding during test sessions, but had no effect on spontaneous motor or food-directed behavior. In contrast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
17
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 62 publications
5
17
1
Order By: Relevance
“…The subiculum has also gained attention in the context of pathophysiological models for a variety of psychiatric conditions, in particular those with a component reflecting maladaptive responses to stress (Herman and Mueller, 2006), including schizophrenia, addiction and mood disorders (Belujon and Grace, 2014; Grace, 2010). Consistent with the presence of functional differentiation across the structure, distinct behavioral consequences of dorsal and ventral subiculum manipulations have been observed in rodents (Andrzejewski et al, 2006; Caine et al, 2001). The dorsal-most regions of the subiculum are known to contain place cells which encode location within the spatial domain (O’Mara, 2006).…”
Section: Introductionsupporting
confidence: 60%
See 2 more Smart Citations
“…The subiculum has also gained attention in the context of pathophysiological models for a variety of psychiatric conditions, in particular those with a component reflecting maladaptive responses to stress (Herman and Mueller, 2006), including schizophrenia, addiction and mood disorders (Belujon and Grace, 2014; Grace, 2010). Consistent with the presence of functional differentiation across the structure, distinct behavioral consequences of dorsal and ventral subiculum manipulations have been observed in rodents (Andrzejewski et al, 2006; Caine et al, 2001). The dorsal-most regions of the subiculum are known to contain place cells which encode location within the spatial domain (O’Mara, 2006).…”
Section: Introductionsupporting
confidence: 60%
“…A final aim was to characterize the functions of the resulting sub-regions with reference to the behavioral taxonomy information in the BrainMap database. We performed a functional characterization of the region via statistical forward and reverse inference, aiming to understand more precisely the region’s role in mnemonic (Carr et al, 2013), spatial (Suthana et al, 2011), motivational (Andrzejewski et al, 2006) and other cognitive processes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The learning paradigm was adapted from previous reports examining the neural systems involved in appetitive learning [26-28]. Briefly, following surgical recovery and food restriction, rats received three days of magazine training in the operant chambers in which they were presented with 45 mg sugar pellets into the food magazine but were not exposed to the lever.…”
Section: Methodsmentioning
confidence: 99%
“…For example, Hernandez et al (Hernandez et al, 2005) demonstrated a profound effect on operant behavior following pre-session D1R blockade in the NAc; however, nose-poking into the food tray (often considered a Pavlovian appetitively conditioned response) was also substantially reduced. Andrzejewski et al (Andrzejewski et al, 2006) found that D1R blockade in vSUB, but not the dSUB, impaired operant learning, but again, motivational deficits were discovered. While it appears likely that DA D1R activation is a crucial for directing the plasticity associated with operant learning, the precise role remains somewhat elusive.…”
Section: Dopamine Involvement In Reward Processing and Plasticitymentioning
confidence: 99%